Pengembangan Modul Pembelajaran Dasar Listrik dan Elektronika Berbasis Course Review Horay - Erikson Ronaldo; Aslimeri Aslimeri (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
Basic Electricity and Electronics are subjects studied by class X students of Electrical Power Installation Engineering competency expertise at SMK Negeri 2 Payakumbuh. Modules are learning materials that are systematically designed based on a certain curriculum and are packaged in the form of learning units and allow them to be studied independently in a certain time unit. Course review horay (CRH) learning is a learning model that attracts motivation using the use of numbers and yells. This study aims to obtain valid and practical CRH-based learning modules in Basic Electricity and Electronics (DLE) subjects. The research method used is R&D (Research & Development) with the 4D model (Define, Design, Develop and Disseminate). The subject of this research is a CRH-based learning module, with research respondents being teachers in Basic Electrical and Electronics subjects and class X TITL students. The questionnaire used in the study was in the form of a Likert scale with a score of 1 to 5. The results of the CRH-based module development research on the distribution of the mediation validation questionnaires obtained the average percentage results on valid criteria, the material validation questionnaire distribution obtained the average percentage results on valid criteria. In distributing the practicality questionnaire the teacher got the average percentage result on the very practical criteria and the student practicality questionnaire got the average percentage result on the practical criteria. The results of this study indicate that the development of CRH-based learning modules made for Basic Electrical and Electronics subjects has been judged valid and practical.